Pengembangan Media Pembelajaran Game Edukasi pada Materi Segi Empat Kelas VII SMPN 1 Wanasaba - M. Khairul Miswari; Amrullah Amrullah; Laila Hayati; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research is a research and development (Research and Development) which aims to develop educational game learning media on the quadrilateral class VII material and determine the feasibility level of educational game learning media on the class VII quadrilateral material. This research was conducted using a 4-D model consisting of stages define, design, develop, and disseminate. The stage define consists of front-end analysis, student analysis, task analysis, concept analysis. The stage design consists of the stage of selecting the format, and the initial design. Then at the stage, development product validation was carried out by experts and product trials involving Class VII SMP students and subject teachers as practitioners. The last stage is the stage, where the disseminated product is distributed in SMP Negeri 1 Wanasaba. The result of this research is a product in the form of educational game learning media on the quadrilateral material for class VII SMP Negeri 1 Wanasaba. Based on the assessments of media experts and material experts as validators, it was found that the educational game learning media developed was in the very good category. Then based on the assessment of the seventh-grade students and the mathematics teacher, that the feasibility of the educational game learning media was obtained in a very good category. This is shown in aspects of cognitive content and aspects of ease of navigation which get a high average score in the very good category. So it can be concluded that this educational game learning media is feasible to be used in mathematics learning activities in the seventh-grade quadrilateral material at SMP Negeri 1 Wanasaba.